Optimization Strategy of Motorized Vehicle Tax (PKB) in Support of Increasing Local Revenue (PAD) (SWOT Analysis Approach) at UPT Pare-Pare Regional Revenue Service - Tawakkal Tawakkal; Muhammad Asdar; Andi Ratna Sari Dewi (Magister Management, Hasanuddin University, 2020)
This study aims to review, analyze and interpret the description of the implementation of local tax collection, in particular, the PKB Motor Vehicle Tax and Motor Vehicle Transfer Fee, and analyze the barriers that occur to further determine strategic steps in an effort to optimally increase local tax revenue. The research used in this research is descriptive method with a qualitative approach. The informants in this study were determined to be two, namely key informants and key informants. The data analysis technique used in this study is to use a SWOT analysis, IFAS Matrix, EFAS Matrix, and SWOT Matrix. The results showed that the Bapenda UPT Parepare Region is currently in quadrant I where the strategy that must be applied in this condition is to support an aggressive growth policy (growth-oriented strategy) in the form of; 1. Optimizing services, 2.Law enforcement and sanctions, and 3. Improving the tax administration system.